2011
DOI: 10.1002/cncr.26475
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality of radical prostatectomy differs by insurance status

Abstract: BACKGROUND: Private insurance status may favorably affect various health outcomes including those associated with radical prostatectomy (RP). We explored the effect of insurance status on 5 short‐term RP outcomes. METHODS: Within the Health Care Utilization Project Nationwide Inpatient Sample (NIS) we focused on RPs performed within the 5 most contemporary years (2003‐2007). We tested the rates of blood transfusions, extended length of stay, intraoperative and postoperative complications, as well as in‐hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17] For example, data from the National Cancer Data Base revealed that individuals with Medicaid were significantly more likely to be diagnosed with cancer at later (stage III or IV) versus earlier stages (stage I) compared with privately insured patients for 11 of 12 cancer sites examined. The largest negative impacts of Medicaid were seen for cancers that can be diagnosed early through appropriate screening, such as breast cancer (odds ratio, 2.7) and melanoma (odds ratio, 3.3).…”
Section: Eliminate Variation Between Medicare Andmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] For example, data from the National Cancer Data Base revealed that individuals with Medicaid were significantly more likely to be diagnosed with cancer at later (stage III or IV) versus earlier stages (stage I) compared with privately insured patients for 11 of 12 cancer sites examined. The largest negative impacts of Medicaid were seen for cancers that can be diagnosed early through appropriate screening, such as breast cancer (odds ratio, 2.7) and melanoma (odds ratio, 3.3).…”
Section: Eliminate Variation Between Medicare Andmentioning
confidence: 99%
“…32 Finally, our results may only be generalizable to the Medicare population and are not intended to be used to predict outcomes in contemporary cohorts. 33 …”
Section: Discussionmentioning
confidence: 97%
“…SES [1,11,12]. The strength of this measure is that particularly for lower SES-associated health insurance plans, an individual review of income is performed on each patient to justify the taxpayer subsidy that often accompanies inclusion in the plan.…”
Section: Pol Scientificmentioning
confidence: 99%
“…Utilization of the healthcare system has been associated with socioeconomic status (SES) [1]. As such, bladder UC may be a disease where there is an association of socioeconomic status and outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation